New observations on the rare physonect Melophysa melo (Siphonophora; Agalmatidae) from the northern Gulf of Mexico - Mapstone, Gill; Youngbluth, Marsh (Zootaxa, 2020)
The rare short-stemmed physonect Melophysa melo typically lives above the thermocline in warm waters of the world’s oceans. In the past this species has been described from fragmented or distorted material, with the last two accounts being published in 1931 and 1954. A new description is given herein with pertinent figures based on nine samples recently collected in the Gulf of Mexico (GoM), including the first detailed illustrations of mature nectophores, and of a well-developed corm. The corm comprises a prominent pneumatophore, a narrow nectosome bearing small attachment lamellae for four nectophores and a much larger short, swollen spiral siphosome bearing eight cormidia. The last five cormidia of this corm are still attached to the pneumatophore, while the oldest three are free, with cormidium one being the oldest and eight the youngest. Two rings of bracteal muscular lamellae occur on the siphosome of this corm, one on the upper surface of each cormidium and a second on the lower surface. Laterally each cormidium supports an upper gonodendron, a zooid meridian bearing palpons and a lower gonodendron. Cormidium one has the most mature gonodendra, and all cormidia have palpons on the zooid meridian, which become progressively mature towards the base. Differences in corm structure from previously described corms are attributed to the younger age of the present two corms. Bracts are re-described from photographic images of both young and mature bracts.